2020
DOI: 10.5194/acp-20-16089-2020
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol vertical distribution and interactions with land/sea breezes over the eastern coast of the Red Sea from lidar data and high-resolution WRF-Chem simulations

Abstract: Abstract. With advances in modeling approaches and the application of satellite and ground-based data in dust-related research, our understanding of the dust cycle has significantly improved in recent decades. However, two aspects of the dust cycle, namely the vertical profiles and diurnal cycles, are not yet adequately understood, mainly due to the sparsity of direct observations. Measurements of backscattering caused by atmospheric aerosols have been ongoing since 2014 at the King Abdullah University of Scie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 104 publications
6
42
0
Order By: Relevance
“…Morning retrieval demonstrates not only the change in particle size but also in the aerosol concentration in the layers below 4000 m. At the same time, vertical pro-files that were obtained several hours before and rely only on COBALD observations demonstrate a significant presence of aerosol in the layer between 6000 and 7000 m. This layer is not observed in the evening observations but is still probably present in the morning profile, although with at slightly lower altitude (5500-6500 m) and with significantly smaller concentration. It should be noted that a similar behaviour of nighttime high-altitude layers was also observed on a regular basis during summertime in a previous study by Parajuli et al (2020). The authors analysed 2 years of MPL data retrieved at night with a similar multi-temporal approach at the KAUST site and concluded that the highaltitude dust was possibly associated with long-range transport of dust from distant sources.…”
Section: Application To Real Observationssupporting
confidence: 67%
See 4 more Smart Citations
“…Morning retrieval demonstrates not only the change in particle size but also in the aerosol concentration in the layers below 4000 m. At the same time, vertical pro-files that were obtained several hours before and rely only on COBALD observations demonstrate a significant presence of aerosol in the layer between 6000 and 7000 m. This layer is not observed in the evening observations but is still probably present in the morning profile, although with at slightly lower altitude (5500-6500 m) and with significantly smaller concentration. It should be noted that a similar behaviour of nighttime high-altitude layers was also observed on a regular basis during summertime in a previous study by Parajuli et al (2020). The authors analysed 2 years of MPL data retrieved at night with a similar multi-temporal approach at the KAUST site and concluded that the highaltitude dust was possibly associated with long-range transport of dust from distant sources.…”
Section: Application To Real Observationssupporting
confidence: 67%
“…The size distribution changes significantly overnight with higher concentration of coarse particles in the morning than in the evening. This could be explained by the diurnal-scale sea breezes becoming stronger by late morning, which mobilize dust locally over the study site (Parajuli et al, 2020). At the same time, nighttime retrieval, which largely depends on inter-pixel temporal constraints due to the low sensitivity of backscatter observations to a detailed size distribution, shows a shape that is somewhat between evening and morning retrievals, although closer to the evening ones.…”
Section: Application To Real Observationsmentioning
confidence: 83%
See 3 more Smart Citations